The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5530/pj.2018.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Antibacterial Activity of Hydro-Alcohol and Aqueous Extracts Obtained from the Lamiaceae Family

Abstract: Context:Plant from the Lamiaceae family are considered as dietary spices and medicinal herbs traditionally used in medicine for the treatment of several pathologies. Objective: Evaluation of the in vitro antibacterial activity of ethanol and aqueous extracts of nine Moroccan plants from the Lamiaceae family against six bacterial strains regularly implicated in toxiinfection. Method: The antibacterial activities of hot (HAE), cold (CAE) aqueous extracts and ethanolic extracts (EE) were evaluated using agar-well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…In a study by Btissam et al [57], hydroethanolic sage extracts obtained through maceration showed generally lower inhibitory effects than those determined for our extracts, with MIC values of 3.12 mg/mL for L. monocytogenes, 1.56 mg/mL for S. aureus, 25 mg/mL for S. enterica and 50 mg/mL for E. coli. Contrarily to our work, in this study, determination of the MBC was possible, with values ranging from 3.12 to 100 mg/mL.…”
Section: Antimicrobial Activitycontrasting
confidence: 61%
“…In a study by Btissam et al [57], hydroethanolic sage extracts obtained through maceration showed generally lower inhibitory effects than those determined for our extracts, with MIC values of 3.12 mg/mL for L. monocytogenes, 1.56 mg/mL for S. aureus, 25 mg/mL for S. enterica and 50 mg/mL for E. coli. Contrarily to our work, in this study, determination of the MBC was possible, with values ranging from 3.12 to 100 mg/mL.…”
Section: Antimicrobial Activitycontrasting
confidence: 61%
“…The antimicrobial potential of plant species has been explored mostly via studies of their essential oils (EOs) [12,13,[22][23][24][25][26][27][28][29][30][31][32][33][34]. Due to the toxic effect exhibited by EOs, it is of utmost importance to explore other plant-derived therapeutic alternatives.…”
Section: Discussionmentioning
confidence: 99%
“…After evaluating the collected publications, a total of 131 papers published since 2000 were considered appropriate for inclusion [ 2 , 4 , 5 , 6 , 7 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72…”
Section: Methodsmentioning
confidence: 99%